ANALYSIS OF THE SYNERGY CONCEPT IN MANAGEMENT OF TOURISM POTENTIAL BASED ON SYIRKAH MUDHARABAH - Dyah Ochtorina Susanti; A’an Efendi (Trunojoyo Madura University, 2022)
This research is motivated by problems that become obstacles in developing the tourism sector. In this regard, the role of investors is needed in assisting in the management of tourism potential by synergizing with local governments. This study uses a normative research method with a statute legal approach to examine the rules governing tourism management in Indonesia, as well as the regulation of syirkah mudharabah; and a conceptual approach to examine the meaning of synergy, syirkah, and mudharabah akads. The results of the study explain that the form of synergy between local governments and investors in managing the tourism sector based on syirkah mudharabah includes 2 (two) forms, namely first, the synergy from the Local Government to investors in the form of providing information to investors regarding infrastructure or other needs that needed in managing tourism potential, reporting the results of coaching and mentoring of Pokdarwis, etc. second, the synergy carried out by investors to the Regional Government, in the form of providing funds following the RAB proposed by the regional government to investors, an investor can provide capital in the form of infrastructure needed by tourist objects.